Atrial Fibrillation and the Prognostic Performance of Biomarkers in Heart Failure. (5th December 2020) - Tan, Eugene S J; Chan, Siew-Pang; Liew, Oi-Wah; Chong, Jenny P C; Leong, Gerard K T; Yeo, Daniel P S; Ong, Hean-Yee; Jaufeerally, Fazlur; Yap, Jonathan; Sim, David; Ng, Tze-Pin; Ling, Lieng-Hsi; et al.
Abstract: Background: Consideration of circulating biomarkers for risk stratification in heart failure (HF) is recommended, but the influence of atrial fibrillation (AF) on prognostic performance of many markers is unclear. We investigated the influence of AF on the prognostic performance of circulating biomarkers in HF. Methods: N-terminal pro-B-type natriuretic peptide (NT-proBNP), mid-regional-pro-atrial natriuretic peptide, C-type natriuretic peptide (CNP), NT-proCNP, high-sensitivity troponin-T, high-sensitivity troponin-I, mid-regional-propeptide adrenomedullin, co-peptin, growth differentiation factor-15, soluble Suppressor of Tumorigenicitiy (sST2), galectin-3, and procalcitonin plasma concentrations were measured in a prospective, multicenter study of adults with HF. AF was defined as a previous history of AF, and/or presence of AF/flutter on baseline 12-lead electrocardiogram. The primary outcome was the composite of HF-hospitalization or all-cause mortality at 2 years. Results: Among 1099 patients (age 62 ± 12years, 28% female), 261(24%) patients had AF. Above-median concentrations of all biomarkers were independently associated with increased risk of the primary outcome. Significant interactions with AF were detected for galectin-3 and sST2. In considering NT-proBNP for additive risk stratification, sST2 (adjusted hazard ratio [AHR]1.85, 95%confidence interval [C.I.] 1.17-2.91) and galectin-3 (AHR1.85, 95%C.I. 1.09-2.45) were independently associated with increased primary outcome only in the presence of AF. The prognostic performance of sST2 was also stronger in AF for all-cause mortality (AF: AHR2.82, 95%C.I. 1.26-6.21; non-AF: AHR1.78, 95% C.I. 1.14-2.76 without AF), while galectin-3 predicted HF-hospitalization only in AF (AHR1.64, 95%C.I. 1.03-2.62). Conclusions: AF modified the prognostic utility of selected guideline-endorsed HF-biomarkers. Application of markers for prognostic purposes in HF requires consideration of the presence or absence of AF. Clinical trial registration: ACTRN12610000374066